How do interest rate changes affect Islamic banks? empirical evidence on Islamic banks in Malaysia - Aliaziz, Muhammad Hafiz; Abdul Rahim, Norhuda; Yahya, Mohamed Hisham (Institut Perakaunan Negara, Jabatan Akauntan Negara Malaysia, 2020)
Purpose; Little empirical evidence has showed that financial systems with dual banking systems are relatively more resilience against many financial crises, especially to changes in interest rate levels. In the same vein, this study investigates the impact of interest rates on Malaysian Islamic banks by analysing the relationship between changes in interest rates on Islamic banks' deposits and financing, Design: The objective is investigated using the ARDL bounds test with 144 observations of monthly data from 2007 to 2018. The unit root tests of Augmented Dickey and Fuller (ADF) and the Phillips-Peron (PP) were conducted, followed by the diagnostic tests of serial correlation and heteroscedasticity, and Cumulative Sum of Recursive Residuals or CUSUM and CUSUM Square stability test to ensure robustness of the results. The robustness of the findings is confimed with diagnostic tests. Findings: The study that interest rates have relationship with both deposit and financing of Malaysian Islamic banks in the long runs. This means that in the long run, when interest rates increases, both deposits and financing of an Islamic bank are still increasing. Futhermore, the religious factor is found to play a role in Malaysian's banking decisions. Practical implications: Firstly, the study highlights that the dual banking system is more resilient than the single banking system as the Islamic banking system is not affected by the conventional interbank rates. However, it also provides evidence that Islamic banks are not entirely independent from the effect of conventional interest rates. Therefore, the Islamic banks need to be attentive to interest rates risk in their risk management, as it could influence the value of their assets and obligations. It also highlights the necessary timing for market to revert back for both institutions’ and investors’ discretion. Secondly, due to all reasons above, the Bank Negara Malaysia needs to be cautious in designing monetary policies as such both government and public sectors can strategize the financing of the country. Originality and value: Providing the most recent sets of data, this study is invaluable to the government, public sectors; financial institutions, investor and fellow academicians. It also adds value to Islamic Bank literature.